Discrepancies in self-reported and actigraphy-based sleep duration are associated with self-reported insomnia symptoms in community-dwelling older adults - Scarlett, Siobhan; Kenny, Rose (My University, 2020)
Objectives: To establish agreement between self-reported and actigraphy-based total sleep time (TST). To determine the impact of self-reported sleep problems on these measurements. Design: Cross-sectional study using data from Wave 3 of The Irish Longitudinal Study on Ageing (2014–2015). Participants: Community-dwelling older adults, aged ≥50 years, with self-reported sleep information and ≥4 days of actigraphy-based TST (n = 1520). Measurement: Self-reported total sleep time, daytime sleepiness, insomnia symptoms (trouble falling asleep, trouble waking too early) measured during a structured self-interview. Actigraphy-based total TST was collected using GENEactiv wrist-worn accelerometers. Demographic characteristics and health information were controlled for. Analyses included descriptive statistics, reliability and agreement analysis using paired t-tests, intra-class correlations and Bland-Altman analysis. Linear regression was used to model associations with measurement discrepancies. Results: Participants reported that they slept 7.0 hours (SD: 1.4, Range: 2.0–13.0 hours) on average, compared to 7.7 hours (SD: 1.2 hours, Range: 3.0–13.0 hours) recorded by accelerometry. Trouble falling asleep or waking too early “most of the time” were associated with under-reporting of sleep by 2.3, and 2.2 hours respectively. Agreement between measurements had an intra-class correlation of 0.18 and wide 95% limits of agreement (-3.90 to 2.55 hours). Under-reporting of sleep was independently associated with insomnia symptoms. Conclusion: The agreement between self-reported and actigraphy-based TST in community dwelling older adults was low. Self-reported insomnia symptoms were independently associated with under-reporting of sleep. Studies seeking to measure sleep duration should consider inclusion of questions measuring experience of insomnia symptoms to account for potential influence on measurements.
PUBLISHED
Keywords: Older population; Ageing; Actigraphy; Sleep; Accelerometer; Insomnia; Sleep duration; Measurement agreement; Ageing